Pedestrian Gap Acceptance and Crossing Decision outside Crossing Facilities along Urban Streets in Malaysia: A Case Study of Rughaya Street, Batu Pahat, Johor, Malaysia (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Walking considered as one of the safest modes oftravel available, sustainable to human society as well asenvironmentally beneficial. In this context, the aim of thisresearch is to investigate pedestrians’ traffic gap acceptanceand crossing decision for Mid-block Street crossing in urbanareas in Malaysia. Pedestrian crossing behaviour atRughaya Street has been examined in terms of the decisionto cross or not the street and size of traffic gaps accepted bypedestrian, as well as the related contributing factors. Afield study was conducted to collect the data of pedestrians’decisions under real mix traffic Condition using videocamera on a typical unsignalized urban street section. JPEGfiles were obtained from video recording by using SnapshotWizard software. The data extracted included trafficcharacteristics such as traffic size, traffic speed, etc.pedestrian individual characteristics such as gender, inaddition to individual behavior such as waiting, frequencyof attempt, etc.). Furthermore, The extracted data wereused to develop and examine a pedestrian gap acceptancemodel based on A lognormal regression model and binarylogistic model by SPSS (22) in order to validate the impactof various parameters on the size of traffic gaps accepted bypedestrians as well as the effect on the decision of pedestrians to cross the street or not.